Ethnicity, nationalism and conflict in and after the Soviet Union : the mind aflame - Tishkov, Valery (London : Sage, 1997)
United Nations Research Institute for Social Development and the International Press Research Institute, Oslo
Keywords: Ethnicity -- Soviet Union; Nationalism -- Soviet Union